Factors Affecting Interest in Revisiting Sharia Hotel - Zakky Fahma Auliya (AL-QARDH, 2019)
This research was conducted due to the phenomenon of a decrease in the stay period of foreign tourists in Indonesia in June 2018 compared to the stay period in June 2017. The independent variables used in this research are the completeness of sharia attributes and hotel image on sharia hotel consumers in Indonesia. The research samples were 100 respondents selected using accidental sampling. The analytical tool used in this research is Smart PLS 3.0. It was found that the completeness of Sharia attributes and hotel image variables influence the interest of revisiting Sharia hotels.